Fenômenos emocionais no contexto explicativo do modo causal de seleção por conseqüências - DARWICH, Rosângela Araújo (Universidade Federal do Pará, 2011)
B. F. Skinner gave rise to radical behaviorism, as the philosophy of a science of behavior, and produced experimental and theoretical arguments that grounded that science. The Skinnerian system distinguished itself from Psychology in the first half of the 20th century, by promoting the physical monism and recommending the approach of overt and covert responses in the context of individual-environment relations. The adherence to the causal mode of selection by consequences in the explanation of the behavior, however, can be viewed as controversial in the context of the analysis of emotional phenomena, for these include operant, but also respondent components. Such issue led to a revision of the theoretical foundations of behavior analysis, resulting in the proposal of an interpretative model of emotional phenomena by means of interrelations among respondent and operant processes. Considering that phylogenetical selection explains the establishment of unconditioned respondent relations, it is investigated if the selectionist model explains conditioned respondent relations in emotional phenomena. The approach of elaborations in behavior analysis resulted in the proposal of an interpretative model of emotional phenomena considering the occurrence of inter-relations among respondent and operant processes. The internal coherence of the Skinnerian interpretative system is preserved by means of the basic statement of that, along ontogenesis, historically established relations with the environment explain the occurrence of overt, covert, respondent and operant responses, as well as those with both components. Considering that conceptual clarity tends to be a prerequisite for intervention, this study contrasted the proposed interpretative model to the context of the accomplishment of functional analysis in the literature of behavior analysis. Preliminarily, the model demonstrated to be a useful interpretative tool, since it enables the understanding of different functions of variables, which take part in the behavioral relations of interest, at a contextualized and historical perspective.